Perceived organizational obstruction: A mediator that addresses source–target misalignment between abusive supervision and OCBs. (21st May 2018) - Mackey, Jeremy D.; McAllister, Charn P.; Brees, Jeremy R.; Huang, Lei; Carson, Jack E.
Summary: We examine perceived organizational obstruction as a mediator in the relationship between abusive supervision and subordinates' organizational citizenship behaviors directed toward organizations. We seek to provide a nuanced understanding of why subordinates who perceive supervisory mistreatment would target organizations with behavioral responses. Specifically, we study the implications of examining relationships between inconsistent sources of social exchange perceptions (e.g., supervisory perceptions) and targets of social exchange behaviors (e.g., organizational responses), which we refer to as social exchange source–target misalignment. Results from 3 studies (Study 1: n = 109; Study 2: n = 213; Study 3: n = 228) demonstrate evidence that abusive supervision is indirectly and negatively associated with organizational citizenship behaviors directed toward organizations through perceived organizational obstruction and that this conditional indirect effect is stronger for subordinates who perceive higher levels of supervisor organizational embodiment than others. Examining the social exchange tandem of perceived organizational obstruction and supervisor organizational embodiment provides a novel and useful means of aligning sources and targets of negative social exchange relationships across subordinates, supervisors, and organizations in order to advance our understanding of the social exchange antecedents and consequences of perceived organizational obstruction.